Trade-Off Between Fertilizer Subsidy And Investment In Indian Agriculture: Special Reference To Assam (International Journal of Food and Nutritional Sciences, 2022)
Public Subsidy is governmental financial support paid to the farmers and agribusinesses to reduce their input expenditure and supplement their income. It helps farmers from any unusual price shocks and crucial for improving agricultural production and productivity. Indian Government has been implementing various schemes and programs under which subsidies are provided for the benefit of small and marginal farmers to reduce their cost of cultivation. Assam Government has also provided various forms of subsidies in fertilizers in agriculture to boost the food security in Assam. Given the limited resources, there arises a trade-off between subsidy in fertilizers and investment in inputs in Agriculture. Therefore, it is important to examine the outcomes of input subsidy in components as fertilizers and compare with government expenditure in the form of investment in technology in order to put public resources in an efficient use. An important issue is with the use of nitrogen fertilizers as it contributes to the greenhouse effect. Nitrogen, an important component in fertilizers has been dubbed as the ‘other greenhouse gas,’ and is as bad as carbon dioxide in global warming, but is not as famous. This paper is an attempt to study the issues related to subsidies in various inputs in the agriculture of Assam. This paper have tried to highlight the risk involved with excessive use of fertilizers to human health and the alternate methods to increase productivity in agriculture in a sustainable way among general public, farming community, health practitioners and agricultural scientists to maximise our social, environmental, economic gains and hope in the years to come.